2016
DOI: 10.1212/nxg.0000000000000044
|View full text |Cite
|
Sign up to set email alerts
|

Overlap between Parkinson disease and Alzheimer disease in ABCA7 functional variants

Abstract: Objective:Given their reported function in phagocytosis and clearance of protein aggregates in Alzheimer disease (AD), we hypothesized that variants in ATP-binding cassette transporter A7 (ABCA7) might be involved in Parkinson disease (PD).Methods:ABCA7 variants were identified using whole-exome sequencing (WES) on 396 unrelated patients with PD and 222 healthy controls. In addition, we used the publicly available WES data from the Parkinson's Progression Markers Initiative (444 patients and 153 healthy contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 30 publications
2
30
0
Order By: Relevance
“…The detection of ABCA7 putative functional variants in participants with PSP, VaD, DLBD, and PA/AGD in this study, in addition to their recent implication in Parkinson disease, 7 suggests that this gene may be contributory to both AD and non-AD neuropathologies. Given evidence of its pleiotropic functions 12,13 including phagocytosis, cell signaling, lipid homeostasis, and Aβ metabolism, it is likely that ABCA7 dysfunction may contribute to both AD-specific and non-AD neuropathologies.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The detection of ABCA7 putative functional variants in participants with PSP, VaD, DLBD, and PA/AGD in this study, in addition to their recent implication in Parkinson disease, 7 suggests that this gene may be contributory to both AD and non-AD neuropathologies. Given evidence of its pleiotropic functions 12,13 including phagocytosis, cell signaling, lipid homeostasis, and Aβ metabolism, it is likely that ABCA7 dysfunction may contribute to both AD-specific and non-AD neuropathologies.…”
Section: Discussionmentioning
confidence: 55%
“…These initial studies were followed by replications and/or identification of additional rare ABCA7 putative LOF mutations in other AD cohorts, 46 in addition to one study in Parkinson disease. 7 …”
mentioning
confidence: 99%
“…Numerous studies have hinted at a shared genetic basis among neurodegenerative diseases. 43,44 Due to the convenience and efficiency of LDSC and the wide accessibility of GWAS summary statistics, several attempts have been made to estimate genetic correlation between neurodegenerative diseases. 9,45 To date, these efforts have not been as successful as similar studies on psychiatric diseases and immunerelated traits.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have not uncovered any disease-associated variants, others were able to identify and functionally validate rare disease-associated variants (Farlow et al 2016;Jansen et al 2017;Sandor et al 2017;Shulskaya et al 2018;Germer et al 2019). Others point towards risk variants that are shared across PD and Alzheimer's disease (AD) (Nuytemans et al 2016). Importantly, none of these studies identified the same rare coding variants.…”
Section: Strategies To Uncover Missing Heritabilitymentioning
confidence: 99%